Dispute settlement reports 2019. World Trade Organization. (Cambridge University Press, 2021)
These are the WTO's authorized and paginated reports in English. They are an essential addition to the library of all practising trade lawyers and a useful tool for students and academics worldwide working in the field of international economic or trade law. DSR 2019: Volume XII contains the decision of the Arbitrator on 'United States - Anti-Dumping and Countervailing Measures on Large Residential Washers from Korea (WT/DS464), Recourse to Article 22.6 of the DSU by the United States', the decision of the Arbitrator on 'European Communities and Certain Member States - Measures Affecting Trade in Large Civil Aircraft (WT/DS316), Recourse to Article 22.6 of the DSU by the European Union', the decision of the Arbitrator on 'United States - Certain Methodologies and their Application to Anti-Dumping Proceedings Involving China (WT/DS471), Recourse to Article 22.6 of the DSU by the United States'.